Comparison of complications in patients of inferior wall myocardial infarction with and without right ventricular infarction - Zaffar, M; Ali Saad, A; Qureshi, B; Bhutta, M; Gill, B; Saleemi, S (2011)
Objective: To compare in-hospital complications in terms of complete heart block and mortality in patients of inferior wall myocardial infarction with or without right ventricular infarction and to see the frequency of right ventricle infarction in patients of inferior wall myocardial infarction. Study Design: Cross-sectional comparative study. Place and Duration of Study: The study was conducted at Chaudary Pervez Elahi Institute of Cardiology, Multan from 7th August 2009 to 6th February 2010. Materials and Methods: 73 patients with inferior ST-segment elevation myocardial infarction were distributed into two groups; one with IWMI only and second with IWMI with RV infarction. Patients with prior MI, pre-existing heart failure, valvular heart disease, pericardial disease, acute pulmonary embolism, significant pulmonary diseases were excluded from the study. The data was analyzed by using software SPSS. The difference in frequencies of complications in two groups was compared using chi square test and a p value of < 0.05 was considered significant. Results: Mean age was 51.95 ± 11.8 years in group 1 and 54.17 ± 12.0 years in group 2. Patients in group 2 had more complications as compared to group 1. The incidence of Complete AV block was 7 (38%) in group 2 vs. 6 (12%) in group 1. (p=<0.001).In-hospital mortality rate was 4 (23%) in group 2 vs. 3 (5%) in group 1 (p=<0.001).The incidence of right ventricular infarction in patients of inferior wall myocardial infarction was noted to be 26%. Conclusion: RVI results in increase in the frequency of complete heart block and mortality in patients of inferior wall myocardial infarction with right ventricular infarction and the incidence of right ventricular infarction in inferior wall MI was 26%.